Multilayer Network Clarifies Prevailing Water Consumption Telecouplings in the United States. Issue 7 (16th July 2021) - Garcia, S.; Gomez, M.; Rushforth, R.; Ruddell, B. L.; Mejia, A.
Abstract: Virtual water flows are used to map the indirect water consumption connections implied by the supply chain of a city, region, or country. This information can be used to manage supply chains to achieve environmental policy objectives and mitigate environmental risks to critical supply chains. A limitation of prior work is that these flows are typically analyzed using monolayer networks, which ignores crucial intersectoral or interlayer couplings. Here, we use a multilayer network to account for such couplings when analyzing blue virtual water flows in the United States. Our multilayer network consists of 115 different regions (nodes), covering the entire conterminous United States; 41 coupled economic sectors (layers); and ∼2 × 10 7 possible links. To analyze the multilayer network, we focus on three fundamental network properties: topological connectivity, mesoscale structure, and node centrality. The network has a high connectivity, with each node being on average connected to roughly 2/3 of the network's nodes. Interlayer flows are a major driver of connectivity, representing ∼54% of all the network's connections. Five different groups of tightly connected nodes (communities) characterize the network. Each community represents a preferred spatial mode of long‐range virtual water interaction within the United States. We find that large (populous) cities have a stronger influence than small ones on network functioning because they attract and recirculate more virtual water through their supply chains. Our results also highlight differences between the multilayer and monolayer virtual water network, which overall show that the former provides a more realistic representation of virtual water flows. Key Points: The United States has five distinctive interregional patterns or spatial modes of long‐range virtual water interactions Large cities have a greater influence than small ones on network functioning because they act as bottlenecks in the flow of virtual water Multilayer network provides a more realistic representation of virtual water flows than single‐layer network Plain Language Summary: Water is a critical input in the production of any product. The total water used in the production of a consumer product, including the water used in the production of the product's raw materials and component parts, is known as the embedded or virtual water. By tracing the water used in the production of a product along all its supply‐chain stages, we map the flow of virtual water between regions for the entire product economy of the United States. This mapping results in a multilayer network of virtual water flows. By analyzing this network, we identify five dominant spatial patterns of virtual water interactions in the United States. Each pattern represents a group of distant regions that strongly depend on each other for the provisioning of virtual water. One pattern shows that a substantial amount of water withdrawn on the Western United States is used to meet cities' demand for products on the Eastern seaboard. The identification of these patterns is a critical step in the design of strategies for making supply chains more resilient to water stress and reducing the impact of economic activity on water‐scarce regions.